Pemanfaatan Antosianin dari Ekstrak Kol Merah (Brassica oleracea var) sebagai Pewarna Dye-Sensitized Solar Cells (DSSC) - Dinasti Dwi Pratiwi; Risa Suryana; Fahru Nuryoshid (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
A prototype of Dye-Sensitized Solar Cells (DSSC) utilizing anthocyanin extract from red cabbage was fabricated. This study aims to determine the wavelength absorption of dye contributed in highest efficiency. The sandwich structure of DSSC consists of TiO2 as working electrode, carbon layer as counter electrode, anthocyanin dye as photosensitizer, and electrolyte as electron transfer media. The absorbance of dye was characterized using UV-Vis spectrophotometer, the efficiency of DSSC was calculated using I-V Meter Keithley, and the quantum efficiency was characterized using IPCE Measurement System. The absorption of dye anthocyanin of red cabbage is 450 nm–580 nm wavelengths, I-V characteristic curves resulted efficiency of 0,029%, and IPCE characteristic resulted highest efficiency at wavelength of 420 nm with efficiency of 0,099%.